ECOINOVATION IN A SUCROENERGY AGROINDUSTRY: THE IMPLEMENTATION OF THE RESIDUAL WATER PROJECT ZERO - Ferreira, Bruna Sousa [UNESP]; Lopes Santos, David Ferreira; Brito Thomaz, Andre Gustavo de [UNESP]; Rebelato, Marcelo Girotto (Univ Nove Julho, 2018)
Increasing global competitiveness, increasing demand for operational efficiency, social and environmental regulations, stakeholder pressure and rapid technological change are increasingly challenging companies to innovate with environmental focus. The objective of the study was the elaboration of a technical report to analyze the potential of eco-innovation projects applied in a sugar-energy plant with a view to the adequate management of the process of abstraction, reuse and disposal of water, aiming at reducing operational costs and improving environmental aspects. The research method used was a single, qualitative and applied case study. The research had as study a sugarcane industry, located in the Northwest region of the state of Minas Gerais. Regarding operational efficiency and cost reduction, the company aims to reduce water resources costs by 20%, which represents savings of approximately R$ 7.4 million per year, despite the investments totaling R $ 1.18 million in structural adjustments for the total implementation of the project. The intention is to improve this project more and more, seeking to expand the eco-innovation in other organizational processes of the company. This study aimed to advance the eco-innovation discussions in agroindustry, since it is a representative sector for the Brazilian economy.
Keywords: Industrial Waste; Sugar Cane; Sustainability; Sustainable Innovation